2014
DOI: 10.1038/hr.2014.120
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-brachial blood pressure index predicts cardiovascular events and mortality in Japanese patients with chronic kidney disease not on dialysis

Abstract: The ankle-brachial blood pressure index (ABPI) has been recognized to have a predictive value for cardiovascular (CV) events and mortality in general or dialysis populations. However, the associations between ABPI and those outcomes have not been fully investigated in predialysis patients. The present study aimed to clarify the relationships between ABPI and both CV events and mortality in Japanese chronic kidney disease (CKD) patients not on dialysis. In this prospective observational study, we enrolled 320 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Atherosclerosis and vascular stiffness are common mechanisms in the pathogenesis of CV diseases, and can be assessed using the ABI and baPWV. In pre-dialysis patients with CKD stages 3–5, Yoshitomi et al reported that ABI can predict CV events, mortality and all-cause mortality [ 46 ]. Atherosclerosis and vascular stiffness may play roles in the link between serum UA and CV abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and vascular stiffness are common mechanisms in the pathogenesis of CV diseases, and can be assessed using the ABI and baPWV. In pre-dialysis patients with CKD stages 3–5, Yoshitomi et al reported that ABI can predict CV events, mortality and all-cause mortality [ 46 ]. Atherosclerosis and vascular stiffness may play roles in the link between serum UA and CV abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies reported results for end-stage renal disease (ESRD) patients on dialysis: 30 studies included subjects exclusively on HD [15,16,19,20,, eight studies included subjects on PD [48][49][50][51][52][53][54][55], three studies included both HD and PD [17,18,56], and six studies reported their subjects were not on dialysis [21,[57][58][59][60][61]. Six studies defined their subjects as having CKD stages 3 to 5, [18,21,58,59,61,62], while only one study described their subjects as CKD stages 3 and 4 [60]. In addition to this, most studies (33/48) reported comorbidity with diabetes mellitus and hypertension.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Aortic stiffness (as evaluated from the carotid femoral pulse wave velocity, PWV) has also emerged as a strong predictor of all-cause and CV mortality in CKD patients [ 12 , 13 ]. Chronic kidney disease patients with either an abnormally high ankle brachial index (ABI) or an ABI below 0.9 had a poor prognosis for all-cause and CV mortality [ 14 , 15 ]. The prevalence of vascular calcification increases steadily with the CKD stage and peaks in stage 5D patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%